Bentuk Mitigasi Bencana Masyarakat Di Dukuh SambungrejoDesa Balerante Kecamatan Kemalang Kabupaten KlatenPasca Erupsi Gunungapi Merapi 2010 - Nugroho, Danang Adi; , Drs. Suharjo, M.S (2016)
Post-eruption of Merapi Volcano, 2010. And to know the role of the Regional Government of the Disaster Mitigation In Sambungrejo Dukuh, Desa Balerante, District Kemalang, Klaten regency Post-eruption of Merapi Volcano in 2010. this Knowing the form of disaster mitigation In Sambungrejo Dukuh, Desa Balerante, District Kemalang, Klaten regency research was conducted using qualitative descriptive method, carried out using field surveys through observation, community interviews. Results of data in getting the mitigation of the Hamlet Sambungrejo, forms of mitigation in Dukuh Sambungrejo are mitigating non structural viewable from public awareness through local government unit, and visible from families making emergency plans and evacuation routes to coordinate their family members to get out of the threat of eruption of Merapi Volcano and can occupy the refugee camps that have been provided by the government and civil society organizations. The role of government in dealing with victims rated quite well, judging from the infrastructure provided by the government to the population that is a refuge decent sertamakanan healthy for the survival of the affected population, especially Hamlet Sambungrejo, the Government also put a sign evacuation route as a form of community safety for out of the path of eruption to the place of refuge.